Investigating the corrosion inhibition mechanism of chitosan for steels in acidic environments: Experimental and computational studies - Kumar D.; Khullar P.; Jain V.; Prakash R.; Rai B. (My University, 2025)
This study investigates the mechanisms of chitosan as a green corrosion inhibitor for mild steel in acidic environments using a combination of experimental and computational methods. Experimental findings demonstrate that even at a low concentration of 25 ppm, chitosan exhibits an impressive inhibition efficiency of approximately 91.5 % at room temperature. Polarization results reveal the mixed inhibitive nature of chitosan, encompassing both cathodic and anodic inhibition. Notably, the inhibition efficiency remains relatively unaffected until temperatures reach approximately 318 K, beyond which it rapidly declines. This has been explained using ReaxFF simulations to be due to thermal degradation of the chitosan molecule. Surface analysis through SEM and AFM techniques highlights the exceptional protective properties of chitosan. Utilizing Density Functional Theory (DFT), explicit adsorption studies of chitosan oligomers on the Fe (001) surface showed the crucial role of N-Fe and O-Fe covalent bonds, along with van der Waals forces, in facilitating the strong inhibition effect of neutral chitosan. However, under strongly acidic conditions, where chitosan amino groups (-NH2) are likely to be protonated (-NH3+), the chemical interactions are limited to O-Fe atoms, resulting in relatively weaker inhibition efficiencies. Thus, this research, for the first time, using DFT and ReaxFF simulations precisely elucidates the specific adsorption mechanisms of chitosan under neutral and protonated conditions and the effect of temperature in deteriorating its inhibition properties respectively. This research also paves the way for future screening and design of novel chitosan derivatives and other polysaccharides as potential corrosion inhibitors for steel using a combination of DFT and ReaxFF calculations. © 2025 Elsevier B.V.